Charge Transfer within Metal-Organic Frameworks: The Role of Polar Node in the Electrocatalysis and Charge Storage. (19th June 2018) - Yu, Jierui; Wyk, Andrea Van; Smith, Tanner; Deria, Pravas
Abstract : Metal-organic frameworks (MOFs) assembled from the photo and redox-active building blocks such as porphyrins and pyrenes, as well as numerous post-synthesis processes that enable incorporation of required chemical functionality within the pores have signified these crystalline molecular assemblies as emerging class of compositions for energy conversion, and storage systems. Electrochemical energy conversion and storage applications require efficient charge transport process within the frameworks. While it is known that a large difference in the redox potentials between the linkers and metal-oxo nodes enforces a hopping type charge transport processes, the impact of the metal-oxo nodes is merely speculative. Part of the reason being the involvement of counter ion that must follow the charge hopping process. This work highlights impacts of -oxo node in the electronic structure of the framework compositions and the role it plays in the electrocatalytic process.